HUBUNGAN PENGETAHUAN SIKAP DAN KARAKTERISTIK IBU TENTANG KANKER SERVIKS DENGAN KEIKUTSERTAAN MELAKUKAN PEMERIKSAAN IVA - Yunita Syahputri Damanik; Efrata Sembiring (Fakultas Kesehatan Masyarakat Institut Kesehatan Deli Husada Delitua, 2018)
Cervical cancer is a malignant tumor that grows the area of ​​the cervix (cervical) and is a disease caused by HPV or Human Papilloma Virus. One of the measures for early detection of cervical cancer is by screening IVA (Visual Inspection Acetic Acid). The purpose of this study was to determine the relationship of knowledge, attitude and characteristic mother of cervical cancer by doing IVA participation. The design of this study is to use a Cross Sectional. The number of samples in this study were as many as 95 people, with a sampling technique using purposive sampling. From the analysis it was found that there are six variables that have a relationship (<0.05), including p-value education by 0:01, the frequency is married with a p-value of 0:00, sexual activity with a p-value of 0:01, with a p-value knowledge 0:00 and the p-value 0:00 while variable that does not have a relationship (> 0.05) among age with p-value 0:21, work with a p-value 0.79, the frequency of pregnancy with a p-value 0:39 and smoking with a p-value of 0:07. From the results of multivariate analysis showed that sexual activity had a meaningful relationship with the participation of IVA examination with p-value OR 3081 0:04 and value. Expected to health professionals to provide information about the dangers of cervical cancer and the importance of conducting the examination IVA.